Software and hardware implementation of smart hands-free set-top box - Weijia SHI; Lin WANG; Liding JIA (Dianxin kexue)
In the background of the development of voice interactive technology,smart speaker becomes a smart home control center,which products in the provision of content entertainment,life services at the same time,and more access to family life scenes.From the smart home under the latest business needs,the increased functional requirements to meet the new business requirements and the requirements of the smart hands-free set-top box were detailed analyzed,the hardware and software implementation scheme of the smart hands-free set-top box to satisfy the new business function was put forward.